VIRUS ELIMINATION FROM IN VITRO POTATO PLANTS - Smyda-Dajmund, Paulina (Plant Breeding and Seed Science, 2017)
The routine and the most effective method of viruses elimination from potato plants is in vitro culture of apical shoots combined with thermo- and/or chemotherapy. At times electrotherapy or cryotherapy is also applied. Elimination of potato viruses by thermotherapy required treatment of infected plants with high tem-perature (35°C - 45°C) for about two weeks. Thermotherapy is useful for elimination of PLRV and PVY from potato plants. In chemotherapy antimetabolite, like ribavirin is used. Chemotherapy is dedicated for elimina-tion of PVM, PVS and PVX. Very often the successful virus elimination require a few cycles of thermo- and/or chemotherapy.